2013
DOI: 10.1111/cdev.12164
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers Default to Canonical Surface‐to‐Meaning Mapping When Learning Verbs

Abstract: Previous work has shown that toddlers readily encode each noun in the sentence as a distinct argument of the verb. However, languages allow multiple mappings between form and meaning which do not fit this canonical format. Two experiments examined French 28-month-olds’ interpretation of right-dislocated sentences (nouni-verb, nouni) where the presence of clear, language-specific cues should block such a canonical mapping. Toddlers (N = 96) interpreted novel verbs embedded in these sentences as transitive, disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 36 publications
0
46
0
2
Order By: Relevance
“…Adults and preschoolers use phrasal prosodic cues to resolve local ambiguity of grammatical categories of familiar words. 17,18 In a recent study 19 French-learning 28-month-olds correctly interpreted the meanings of transitive sentences (e.g., Il mange le canard; "it eats the duck") versus right-dislocated sentences (e.g., Il mange, le canard; "the duck eats") based on their distinct prosody, although they failed to do so for a novel verb whose meaning was newly taught.…”
mentioning
confidence: 98%
“…Adults and preschoolers use phrasal prosodic cues to resolve local ambiguity of grammatical categories of familiar words. 17,18 In a recent study 19 French-learning 28-month-olds correctly interpreted the meanings of transitive sentences (e.g., Il mange le canard; "it eats the duck") versus right-dislocated sentences (e.g., Il mange, le canard; "the duck eats") based on their distinct prosody, although they failed to do so for a novel verb whose meaning was newly taught.…”
mentioning
confidence: 98%
“…Subsequent studies using this paradigm have shown the same result (e.g. Arunachalam, 2013;Arunachalam et al, 2013;Arunachalam & Waxman, 2010;Dautriche et al, 2014;Gertner & Fisher, 2012;Jin & Fisher, 2014;Messenger et al, 2015;Yuan et al, 2012).…”
Section: Research Highlightsmentioning
confidence: 65%
“…Gleitman, 1990;Landau & Gleitman, 1985), and specifically have shown that toddlers have early and robust knowledge that transitive frames can describe causative events, in which one event participant acts on and affects another (e.g. Arunachalam, 2013;Arunachalam, Escovar, Hansen, & Waxman, 2013;Arunachalam & Waxman, 2010;Dautriche et al, 2014;Fernandes, Marcus, Di Nubila, & Vouloumanos, 2006;Fisher, 1996Fisher, , 2002Jin & Fisher, 2014;Lee & Naigles, 2008;Lidz, Gleitman, & Gleitman, 2003;Messenger, Yuan, & Fisher, 2015;Naigles, 1996;Yuan & Fisher, 2009;Yuan, Fisher, & Snedeker, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 21‐month‐olds misinterpreted the novel verb in ‘the boy and the girl are gorp ing’ to mean an event where the boy is doing something to the girl . Similarly, French‐learning 28‐month‐olds disregarded the prosodic cue in right‐dislocated sentences like ‘il dase , the bébé (he is das ing, the baby; meaning ‘the baby is das ing’), and misinterpreted the intransitive verb as transitive . And recent work demonstrates that adults and infants conceptualize event participants such as instruments of actions as event participants, which should lead learners using a counting‐the‐nouns heuristic to the erroneous hypothesis that instruments must be encoded in a sentence containing the verb, though in fact they are optional (e.g., Emeril cut the tomato (with a knife)) .…”
Section: Identifying the Conceptmentioning
confidence: 99%
“…87 Similarly, French-learning 28-month-olds disregarded the prosodic cue in right-dislocated sentences like 'il dase, the bébé (he is dasing, the baby; meaning 'the baby is dasing'), and misinterpreted the intransitive verb as transitive. 88 And recent work demonstrates that adults and infants conceptualize event participants such as instruments of actions as event participants, which should lead learners using a counting-the-nouns heuristic to the erroneous hypothesis that instruments must be encoded in a sentence containing the verb, though in fact they are optional (e.g., Emeril cut the tomato (with a knife)). 89 Therefore, the degree to which learners can make use of syntactic bootstrapping depends on their developing language skills as well as their conceptualization of the referent event.…”
Section: Linguistic Cuesmentioning
confidence: 99%